Unique Presentation of Cerebellopontine Angle Choroid Plexus Papillomas: Case Report and Review of the Literature - Anderson, Mark; Babington, Parker; Taheri, Reza; Diolombi, Mairo; Sherman, Jonathan H. (Journal of Neurological Surgery Reports, 2014)
Objectives We present the case of a choroid plexus papilloma (CPP) in the cerebellopontine angle (CPA), describe the different appearances of CPPs with a variety of imaging techniques, and discuss the differential diagnosis of CPA tumors.Participant and Design We report the case of a 52-year-old woman with headache, tinnitus, and unilateral hearing impairment whose preoperative magnetic resonance imaging revealed a heterogeneously enhancing CPA mass that extended into the internal auditory canal.Main Outcome Measures, Results, and Conclusion The preoperative imaging appearance of the lesion was most consistent with that of a schwannoma. Postoperative histopathologic examination found the tumor to be a CPP with cuboidal epithelial cells overlying fibrovascular stroma. CPPs are rare benign central nervous system neoplasms arising from choroid plexus epithelium. The most common site of presentation is in the fourth ventricle in adults and the lateral ventricles in children. CPPs rarely occur in the CPA, and when they do, clinical-radiologic diagnosis is difficult due to both the rarity of this presentation and to nonspecific radiological features.
Keywords: cerebellopontine angle; choroid plexus papilloma